1998
DOI: 10.1289/ehp.106-1533225
|View full text |Cite
|
Sign up to set email alerts
|

Volatile N-nitrosamine formation after intake of nitrate at the ADI level in combination with an amine-rich diet.

Abstract: Formation of nitrite from ingested nitrate can result in several adverse health effects and implies a genotoxic risk as a consequence of endogenous formation of carcinogenic N-nitroso compounds. We studied the formation of volatile N-nitrosamines after intake of nitrate at the acceptable daily intake (ADI) level in combination with a fish meal rich in amines as nitrosatable precursors. Twenty-five volunteers consumed this meal during 7 consecutive days; a diet low in nitrate was consumed during 1 week before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 38 publications
4
74
1
2
Order By: Relevance
“…Adducts 13, 16 and 17 were directly identified by the spectral data described below. Similarly, Figure 1C shows a peak corresponding to (M + H) + of dThd adduct(s) (18,19, and/or 20), which also disappeared upon NTH ( Figure 1G). We could not obtain NMR data on this dThd adduct(s).…”
Section: Resultsmentioning
confidence: 78%
“…Adducts 13, 16 and 17 were directly identified by the spectral data described below. Similarly, Figure 1C shows a peak corresponding to (M + H) + of dThd adduct(s) (18,19, and/or 20), which also disappeared upon NTH ( Figure 1G). We could not obtain NMR data on this dThd adduct(s).…”
Section: Resultsmentioning
confidence: 78%
“…NOC can be found in normal human feces, urine and saliva, and it has been suggested that this is due to in vivo nitrosation of ingested secondary and tertiary amines (Kakizoe et al, 1979). This process may be further catalyzed by the presence of heme iron, which is also present in processed meat (Cross, Pollock, & Bingham, 2003;Vermeer, Pachen, Dallinga, Kleinjans, & van Maanen, 1998). Recently, human studies have demonstrated that indeed under normal dietary conditions urinary markers of exposure to N-nitroso compounds are associated with micronucleus frequencies, a validated marker of carcinogenic risk, as well as with gene expression changes that are involved in cancer development (Hebels, Jennen, et al, 2011).…”
Section: N-nitroso Compoundsmentioning
confidence: 99%
“…Epidemiological studies have not provided any evidence that there is an increased risk of cancer related to high nitrate intake from sources other than vegetables. In some cases studies revealed a negative correlation between nitrate intake and gastric cancer (Beresford, 1985) because vegetables are an excellent source of vitamins, minerals and biologically active compounds (Vermeer et al, 1998).…”
Section: Carcinogenicitymentioning
confidence: 99%